2023
DOI: 10.3390/su151411103
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy: A Curse or Blessing—International Evidence

Abstract: The development of renewable energy has effectively promoted the process of reaching global carbon neutrality. However, the academic community has not reached a consensus on whether the development of renewable energy will inhibit economic growth. The crux of the debate centers around whether renewable energy paradigms ignore differences in the structure of factor endowments across countries. The panel data of 125 countries from 1990 to 2021 were used to perform group regression for countries with different fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…From the mid-1970s onwards, many studies of the energy crisis were conducted due to oil shocks. Common solutions might effectively reduce energy consumption, including the development of eligible renewable energy and the construction and use of green energy equipment to reduce carbon emissions [22,23]. The design, development and dissemination of appropriate renewable energy technology are important not only to meet the growing energy requirements for economic growth, but also for improvement in the quality of human life [24,25].…”
Section: Renewable Energymentioning
confidence: 99%
“…From the mid-1970s onwards, many studies of the energy crisis were conducted due to oil shocks. Common solutions might effectively reduce energy consumption, including the development of eligible renewable energy and the construction and use of green energy equipment to reduce carbon emissions [22,23]. The design, development and dissemination of appropriate renewable energy technology are important not only to meet the growing energy requirements for economic growth, but also for improvement in the quality of human life [24,25].…”
Section: Renewable Energymentioning
confidence: 99%
“…Currently, the global energy structure has been reformed by renewable energy sources to cope with the increasing demands and environmental pollution issues of traditional fuels [1,2]. However, the application of renewable energy sources has long been plagued by its instability, seasonality, regionality, low conversion efficiency, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Previous energy transitions have shown that energy system transformations or fuel switching depend on a variety of factors, including policy, price, and availability, and research has shown that those changes have been neither linear nor smooth [1]. With increased focus on the importance of climate change and the need to limit global warming to 1.5 • C, there has been a proliferation of research on how to manage and facilitate the upcoming energy transition [2][3][4][5]. Demand-side and supply-side changes are required and they will need to occur in an integrated manner to minimize disruptions [6][7][8].…”
Section: Introductionmentioning
confidence: 99%